Normative Values of Peripapillary Retinal Nerve Fiber Layer Thickness in a Middle Eastern Population - Mouna M. Al-Sa’ad; Amjad T. Shatarat; Justin Z. Amarin; Darwish H. Badran (Journal of Ophthalmology)
Purpose. Peripapillary retinal nerve fiber layer (pRNFL) thickness is subject to high variability. Normative values of pRNFL thickness remain undocumented in the Middle East. The aim of our study is to assess the normative values of pRNFL thickness in a Middle Eastern population. Methods. A retrospective chart review of 74 patients was conducted. Outpatients who had presented to the ophthalmology clinic at the Jordan University Hospital between January 2016 and July 2018 were consecutively sampled. Measurements had been recorded using Fourier-domain optical coherence tomography. Multivariable regression models were developed to generate predicted normative values with adjustments to candidate confounders. Results. The mean global pRNFL thickness was 99 ± 11 μm. The mean quadrantic pRNFL thickness increased from the nasal quadrant (75 ± 16 μm) to the temporal (82 ± 20 μm), superior (114 ± 20 μm), and inferior (125 ± 20 μm) quadrants. Gender and eye sidedness did not contribute to the variability in pRNFL thickness. The relationship between aging and pRNFL thinning is independent of diabetes mellitus type 2 and systemic hypertension. Both systemic conditions significantly predicted pRNFL changes despite negative fundoscopic findings. Conclusions. Our set of predicted normative data may be used to interpret measurements of pRNFL thickness in Middle Eastern patients. Our findings suggest that systemic conditions with potential ocular manifestations may require consideration in predictive models of pRNFL thickness, even in the absence of gross fundoscopic findings. Normative data from additional Middle Eastern populations are required to appraise our models, which adjust for common clinical confounders.